Guided tour to The Villa Stein (2019)
This is a reflection about The Villa Stein, one of the most Le Corbusier’s emblematic houses, built in 1928 in Garches near Paris, and one of the most significant works in the early Modern Movement. Some questions come out from te house, for example, where did the forms of this house come from? What were the design methods used by Le Corbusier? To answer these, the author offers to the reader a route that goes from the outside to the interior and later to the garden of the house (as if it were a guided tour), in which we will find contrasted and unexpected situations that will keep our attention  on. As we advance in the course we can find the interpretations suggested by the author, which give an explanation of the references and the compositional methods used by the architect. In short, this is an exercise that seeks to reveal the ideas that gave rise to the shape of the house and elucidate some references and methods of design employed by Le Corbusier.